2017
DOI: 10.1021/acsami.7b13929
|View full text |Cite
|
Sign up to set email alerts
|

Core–Shell Silver Nanoparticles in Endodontic Disinfection Solutions Enable Long-Term Antimicrobial Effect on Oral Biofilms

Abstract: To achieve effective long-term disinfection of the root canals, we synthesized core-shell silver nanoparticles (AgNPs@SiO) and used them to develop two irrigation solutions containing sodium phytate (SP) and ethylene glycol-bis(β-aminoethyl ether)N,N,N',N'-tetraacetic acid (EGTA), respectively. Ex vivo studies with instrumented root canals revealed that the developed irrigation solutions can effectively remove the smear layer from the dentinal surfaces. Further in vitro experiments with single- and multispecie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 40 publications
0
30
0
1
Order By: Relevance
“…Furthermore, coupling with the anti-S. aureus α-toxin monoclonal antibody ensured that ISMN could selectively act on the biofilm, which would not only improve the efficacy of ISMN against biofilms, but could also reduce drug dosage and decrease adverse drug reactions. The hydrophobic properties of the bacterial cell wall have also been shown to impact liposomes penetration and enhance drug mobility through the biofilm matrix (28). Compared with topical antimicrobials, which have difficulty penetrating the biofilm matrix, immunoliposomes could easily combine with and enter into bacterial biofilm; the retention of immunoliposomes in the biofilm could facilitate drug release in close proximity of the bacteria over extended periods of time (22), which is extremely important for effective biofilm eradication.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, coupling with the anti-S. aureus α-toxin monoclonal antibody ensured that ISMN could selectively act on the biofilm, which would not only improve the efficacy of ISMN against biofilms, but could also reduce drug dosage and decrease adverse drug reactions. The hydrophobic properties of the bacterial cell wall have also been shown to impact liposomes penetration and enhance drug mobility through the biofilm matrix (28). Compared with topical antimicrobials, which have difficulty penetrating the biofilm matrix, immunoliposomes could easily combine with and enter into bacterial biofilm; the retention of immunoliposomes in the biofilm could facilitate drug release in close proximity of the bacteria over extended periods of time (22), which is extremely important for effective biofilm eradication.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 They have also been widely exploited as novel bacteria-resistant products for the long-term disinfection of root canals, preventing the formation of E. faecalis biolms. 40 Most importantly, biolm-associated R. solanacearum cells can produce a variety of extracellular polymeric substances (EPS) along with various proteins, which are known to be key pathogenic factors when a pathogen infects host roots in the rhizosphere. 41 Thus, although there was no change in biolm formation during the 12 h treatment period, our results clearly demonstrated that the application of CuONPs could effectively exert antibacterial activity against R. solanacearum by disturbing the invasion course aer a longer incubation time.…”
Section: Inhibition Of Bacterial Biolm Formationmentioning
confidence: 99%
“…Of all the metals investigated as antibacterial agents, silver (Ag) NPs have perhaps proved the most useful against a wide spectrum of microorganisms . Silver and its compounds can possess potent bactericidal activity and have been developed into NPs for potential drug treatments . The antimicrobial efficacy of silver NPs is determined by size, shape, and nature of the capping agents.…”
Section: Classification Of Antimicrobial Nanoparticlesmentioning
confidence: 99%